PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DI PEMERINTAHAN KOTA PALOPO YANG DIMODERASI DESENTRALISASI DAN MOTIVASI - A Ziaul Assaad (MUAMALAH, 2015)
The purpose of this study is to examine the effect of the interaction of structural officials in Palopo City government to participate in the process of budgetary management on managerial performance and to evaluate decentralization, motivation as a moderating variable in strengthening the effects of budgetary participation on managerial performance. This research concludes that 1). The participation of budgetary management had significant effect on the managerial performance. The officials involved in budgetary management were aware that their participation in budgetary management can improve managerial performance. 2). Participation in the preparation of the budget had a significant impact with increased performance on decentralization, specially in the municipality Palopo. 3). The Participation in budgetary management did not have a significant effect with improved performance on motivation, especially motivation of structural officials of Palopo Government